Wireless Network Security - Xiao, Yang; Shen, Xuemin; Du, Ding-Zhu (Signals and Communication Technology, 2007)
This timely volume, Wireless Network Security, provides broad coverage of wireless security issues including cryptographic coprocessors, encryption, authentication, key management, attacks and countermeasures, secure routing, secure medium access control, intrusion detection, epidemics, security performance analysis, security issues in applications, and much more. The contributions identify various vulnerabilities in the physical layer, MAC layer, IP layer, transport layer, and application layer, and focus on ways for strengthening security mechanisms and services throughout the layers. The book includes 15 rigorously refereed chapters from prominent international researchers working in this subject area. The material serves as a useful reference for researchers, graduate students, and practitioners seeking solutions to wireless and mobile security related issues.